2010
DOI: 10.1096/fj.09-144436
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lysophospholipid suppresses hepatic fatty acid oxidation: the molecular link between group 1B phospholipase A2and diet‐induced obesity

Abstract: Decrease in fat catabolic rate on consuming a high-fat diet contributes to diet-induced obesity. This study used group 1B phospholipase A(2) (Pla2g1b)-deficient mice, which are resistant to hyperglycemia, to test the hypothesis that Pla2g1b and its lipolytic product lysophospholipid suppress hepatic fat utilization and energy metabolism in promoting diet-induced obesity. The metabolic consequences of hypercaloric diet, including body weight gain, energy expenditure, and fatty acid oxidation, were compared betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 40 publications
6
63
0
1
Order By: Relevance
“…However, whereas the Pla2g1b +/+ mice showed progressive elevation from our laboratory have shown that Pla2g1b inactivation is protective against diet-induced obesity and hyperglycemia in mice ( 20,21 ), suggesting that Pla2g1b contributes directly to these diet-induced metabolic disorders. The Pla2g1b Ϫ / Ϫ mice are resistant to diet-induced obesity due to their ability to sustain elevated energy expenditure via increased hepatic fatty acid oxidation when fed a hypercaloric diet ( 22 ). The elevated fatty acid catabolic rate in the liver of Pla2g1b Ϫ / Ϫ mice also reduces dietary fat availability to other metabolically active tissues, thereby increasing their dependence on glucose as a fuel source and resulting in protection against diet-induced glucose intolerance and hyperglycemia ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whereas the Pla2g1b +/+ mice showed progressive elevation from our laboratory have shown that Pla2g1b inactivation is protective against diet-induced obesity and hyperglycemia in mice ( 20,21 ), suggesting that Pla2g1b contributes directly to these diet-induced metabolic disorders. The Pla2g1b Ϫ / Ϫ mice are resistant to diet-induced obesity due to their ability to sustain elevated energy expenditure via increased hepatic fatty acid oxidation when fed a hypercaloric diet ( 22 ). The elevated fatty acid catabolic rate in the liver of Pla2g1b Ϫ / Ϫ mice also reduces dietary fat availability to other metabolically active tissues, thereby increasing their dependence on glucose as a fuel source and resulting in protection against diet-induced glucose intolerance and hyperglycemia ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…mice can be abrogated with lysophosphatidylcholine (LPC) supplementation ( 22,23 ). Although the effects of hypercaloric diet and Pla2g1b inactivation upon glucose response and homeostasis had been examined, whether Pla2g1b inactivation also infl uences plasma lipid homeostasis in response to hypercaloric feeding has not been determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major pathways for the formation of LPA is through the action of autotaxin on LysoPC ( 23 ). A major source of intestinal LysoPC is through the action of PLA2G1B (45)(46)(47)(48)(49)(50). PLA2G1B is a pancreatic PLA 2 that hydrolyzes fatty acids at the sn -2 position of phospholipids in the lumen of the small intestine.…”
Section: Searching For Natural Sources Of Intestinally Derived Lpamentioning
confidence: 99%
“…PLA2G1B is a pancreatic PLA 2 that hydrolyzes fatty acids at the sn -2 position of phospholipids in the lumen of the small intestine. The uptake of LysoPC formed by the action of PLA2G1B was reported to be very effi cient and stimulated VLDL production ( 47 ). We hypothesized that LysoPC produced by the action of PLA2G1B on dietary unsaturated phospholipids might be a good substrate for the formation of unsaturated LPA in the enterocytes of the small intestine because i ) LysoPC is readily absorbed into the enterocytes of the small intestine ( 49 ), and ii ) autotaxin is highly expressed in the enterocytes of the small intestine ( 51 ).…”
Section: Searching For Natural Sources Of Intestinally Derived Lpamentioning
confidence: 99%